Audit Board Of Indonesia’s Supervision Duty Reviewed From Islamic Law Perspective For Acceleration Of Sustainable Development - Palmawati Taher; Dwi Andayani Bs; Muhammad Rizqi Fadhlillah (Fiat Justisia: Jurnal Ilmu Hukum, 2022)
State Financial Auditing Board, also known as the BPK, whose job is to look into the management and responsibility of state finances, shared the same principle with Mazhalim Region, an institution in Islamic state administration that looks into cases involving state property. In Islam, laws are typically made to safeguard wealth from those who are overly ambitious or greedy for things that a Muslim would consider to be enough to satisfy their needs. The principle is crystallized in Muslim life: Amar ma'ruf nahi mungkar became the leading guide in achieving a better life. The position of the BPK in the Indonesian and Mazhalim Region in Islamic State administration systems concerning accelerating sustainable development is attracting considerable interest in this paper to see the supervision of the BPK's task from an Islamic perspective. Since the law is conceptualized as a social norm or rule that governs everyone's behavior, it is the primary focus of this study. Thus, compiling positive law, principles, doctrines of law, legal discovery in concreto cases, systematic law, synchronization levels, legal comparisons, and legal history are concerns of normative legal research.